Strong Interfacial Charge Trapping in Ultrathin SrRuO3on SrTiO3Probed by Noise Spectroscopy - Lee, Jung Woo; Kim, Jiyeong; Eom, Kitae; Jeon, Jaeyoung; Kim, Young Chul; Kim, Hwan Sik; Ahn, Yeong Hwan; Kim, Sungkyu; Eom, Chang Beom; Lee, Hyungwoo (Journal of Physical Chemistry Letters, 2022)
SrRuO3 (SRO) has emerged as a promising quantum material due to its exotic electron correlations and topological properties. In epitaxial SRO films, electron scattering against lattice phonons or defects has been considered as only a predominant mechanism accounting for electronic properties. Although the charge trapping by polar defects can also strongly influence the electronic behavior, it has often been neglected. Herein, we report strong interfacial charge trapping in ultrathin SRO films on SrTiO3 (STO) substrates probed by noise spectroscopy. We find that oxygen vacancies in the STO cause stochastic interfacial charge trapping, resulting in high electrical noise. Spectral analyses of the photoinduced noise prove that the oxygen vacancies buried deep in the STO can effectively contribute to the charge trapping process. These results unambiguously reveal that electron transport in ultrathin SRO films is dominated by the carrier number fluctuation that correlates with interfacial charge trapping.
Keywords: Charge-trapping; Correlation properties; Electronic behaviors; Interfacial charge; Lattice phonons; Noise spectroscopy; SrTiO3 substrates; Stochastics; Topological properties; Ultra-thin